A 1.51 V pH neutral redox flow battery towards scalable energy storage. Issue 15 (27th March 2019) - Luo, Jian; Wu, Wenda; Debruler, Camden; Hu, Bo; Hu, Maowei; Liu, T. Leo
Abstract : A 1.51 V pH neutral (SPr)2 V/Br − AORFB with high energy and power densities was demonstrated for scalable energy storage. Abstract : Aqueous redox flow batteries using low-cost organic and inorganic active materials have received growing interest for sustainable energy storage. In this study, a low-cost, high redox potential (1.08 V vs. NHE) and high capacity ammonium bromide (NH4 Br, 214.4 A h L −1 ) catholyte was coupled with an organic viologen anolyte to demonstrate 1.51 V high voltage (SPr)2 V/Br − aqueous redox flow batteries under pH neutral conditions for the first time. Benefitting from the high water solubility of both the NH4 Br catholyte and (SPr)2 V anolyte, the newly designed (SPr)2 V/Br − organic flow battery was operated at up to 1.5 M and an energy density of up to 30.4 W h L −1 . Using multiwall carbon nanotubes as an electrochemical additive for the Br3 − /Br − redox couple, the highly energy dense (SPr)2 V/Br − flow battery manifested outstanding current performance, up to 78% energy efficiency at 40 mA cm −2 current density and 227 mW cm −2 power density, the highest power density known for pH neutral organic flow batteries.